Primary pulmonary meningioma: a case report and literature review - Liu, Qinmin; Luo, Shuhua; Guo, Meijuan (Frontiers in Oncology, 2025)
Meningioma is a common tumor of the central nervous system, with occasional occurrences outside this region. Herein, we present a case of primary pulmonary meningioma (PPM) in a 64-year-old male who was both a non-smoking and non-drinking. Computed tomography (CT) imaging unveiled a solitary, lobulated, and well-circumscribed solid nodule in the posterior basal segment of the right lower lobe. This nodule exhibited a mean attenuation of approximately 31.6 Hounsfield units (HU). Upon contrast-enhanced CT, the lesion demonstrated persistent moderate enhancement, with attenuation values rising to 69.7 HU in the arterial phase and further increasing to 78.2 HU in the venous phase. Positron emission tomography-computed tomography (PET-CT) scanning revealed mildly increased fluorodeoxyglucose (FDG) uptake within the lesion, with a maximum standardized uptake value (SUVmax) of approximately 2.4. The patient underwent uniportal video-assisted thoracoscopic surgery (VATS) for wedge resection of the nodule in the right lower lobe. Histopathological examination subsequently confirmed the diagnosis of meningioma, specifically the transitional type classified as WHO grade I. Postoperatively, the patient recovered well, with follow-up chest CT scans demonstrating no evidence of tumor recurrence. PPM is recognized as an extremely rare meningioma of ectopic origin, predominantly benign in nature, and often presenting with asymptomatic clinical manifestations. CT imaging typically shows single or multiple nodules with clearly defined boundaries, uniform density, and smooth edges. Notably, surgical resection has proven to be an effective treatment strategy for PPM.